2020
DOI: 10.3389/fphar.2020.00768
|View full text |Cite
|
Sign up to set email alerts
|

Tubeimoside I Antagonizes Yoda1-Evoked Piezo1 Channel Activation

Abstract: Piezo1, a mechanosensitive Ca 2+ -permeable non-selective cationic ion channel protein, is involved in a wide range of biological processes and plays crucial roles in vascular development. However, the pharmacology of this protein is in its infancy. Yoda1, the first specific chemical activator of Piezo1 channels, can activate Piezo1 in absence of mechanical stimulation. Hence, we sought to identify inhibitors of Yoda1 from Traditional Chinese Medicine (TCM). Intracellular Ca 2+ measurements were conducted in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Jedi1/2 is a new type of hydrophilic Piezo1 chemical activator, which acts through the peripheral blades and uses a peripheral lever-like device composed of blades and light beams to gate the central ion conduction hole ( 142 ). Recently, an analogue of Yoda1, named Dooku1 ( 147 ), and tubeimoside I (TBMS1) identified in traditional Chinese medicine ( 148 ), reversibly antagonizes the activation of Piezo1 induced by Yoda1 through competition for specific channel binding sites.…”
Section: Pharmacology and Physical Regulation Of Piezo1 Channelmentioning
confidence: 99%
“…Jedi1/2 is a new type of hydrophilic Piezo1 chemical activator, which acts through the peripheral blades and uses a peripheral lever-like device composed of blades and light beams to gate the central ion conduction hole ( 142 ). Recently, an analogue of Yoda1, named Dooku1 ( 147 ), and tubeimoside I (TBMS1) identified in traditional Chinese medicine ( 148 ), reversibly antagonizes the activation of Piezo1 induced by Yoda1 through competition for specific channel binding sites.…”
Section: Pharmacology and Physical Regulation Of Piezo1 Channelmentioning
confidence: 99%
“…RR If administered from extracellular side, inhibits the inward rather than outward current of mPiezo1/2 alone, suggesting its pore-inhibiting mechanism 45 . Recent studies reported the recognition of other molecules, including Yoda1 analog named Dooku1 172 and the most recent compound Tubeimoside1 (TBMS1) extracted from Bolbostemma 173 , both with reversible antagonizing capability of Yoda1-evoked Piezo1 trigger (Table 3 ). They were reported to exert their effect through selective binding site competition with Yoda1.…”
Section: Piezo1 Pharmacologymentioning
confidence: 99%
“…In our study, we found that IR decreased expression of SIRT1, but TBM could not reverse expression of SIRT1 (Figure S5 ). Recently, TBM has been reported to antagonize Yoda1-evoked Piezo1 channel activation [ 63 ]. Also, Piezo1 is proposed to be a vital factor that leads to cerebral ischemia-reperfusion injury [ 64 ].…”
Section: Discussionmentioning
confidence: 99%